2020
DOI: 10.1177/1099800420931183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Enrichment on Neurotrophins in an MPTP-Induced Parkinson’s Disease Animal Model: A Randomized Trial

Abstract: The aim of this study was to investigate the effect of environmental enrichment (EE) on neurotrophin expression in an animal model of Parkinson’s disease (PD). PD was induced via intraperitoneal injection of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). Male mice ( N = 42) were randomly divided into 3 groups: control, MPTP + standard condition (SC), and MPTP + EE. The groups were raised separately for 28 days. On Day 21 they received 1 injection (20 mg/kg MPTP or saline for MPTP and control groups, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The p75NTR, encoded by NGFR, was found to play a critical role in the selective neuronal death of dopaminergic neurons in the substantia nigra, as well as in the pathogenesis and progression of PD (Li et al, 2019). One study confirmed that environmental enrichment exerts neuroprotective effects on the survival of dopaminergic neurons through inactivation of the p75NTR-mediated signalling pathway via the binding of proNGF to p75NTR (Cho & Kang, 2020). Another study demonstrated significant increase in p75NTR upregulation following kainic acid insult in the substantia nigra of rat model, suggesting that p75NTR may function importantly in neuronal cell survival or excitotoxic degeneration of dopamine neurons in the substantia nigra in the pathogenesis and development of PD in human beings (Wang et al, 2008).…”
Section: The Role Of P75ntr In Pdmentioning
confidence: 99%
“…The p75NTR, encoded by NGFR, was found to play a critical role in the selective neuronal death of dopaminergic neurons in the substantia nigra, as well as in the pathogenesis and progression of PD (Li et al, 2019). One study confirmed that environmental enrichment exerts neuroprotective effects on the survival of dopaminergic neurons through inactivation of the p75NTR-mediated signalling pathway via the binding of proNGF to p75NTR (Cho & Kang, 2020). Another study demonstrated significant increase in p75NTR upregulation following kainic acid insult in the substantia nigra of rat model, suggesting that p75NTR may function importantly in neuronal cell survival or excitotoxic degeneration of dopamine neurons in the substantia nigra in the pathogenesis and development of PD in human beings (Wang et al, 2008).…”
Section: The Role Of P75ntr In Pdmentioning
confidence: 99%
“…These results indicate that EE could decrease the loss of dopaminergic neuronal cells in the SNpc and striatum. 33 In 6-hydroxydopamine (6-OHDA) PD models, increased cell proliferation has been observed in the SN after EE rearing. 34 In addition, decreased striatal dopaminergic loss and increased expression of cells positive for ionized calcium binding adaptor molecule 1 (Iba-1), nerve antigen 2 (NG2), and glial fibrillary acidic protein (GFAP) were also described.…”
Section: Brain Disorders and Enriched Environmentmentioning
confidence: 99%
“…Eight included studies evaluated tumor volume, which is usually measured using the equation (Volume = length × width 2 × π/6) and expressed in mm 3 and percentage [10,[12][13][14][15][16][17][18]. The results showed that EE was able to significantly reduce tumor volume in mice with colon, melanoma, breast, glioma, pancreatic, liver, and lung cancer.…”
Section: Tumor Volume Weight Size and Angiogenesis After Environmenta...mentioning
confidence: 99%